Knowledge, attitudes, and practices regarding prevention of peripheral vascular complications in patients with type 2 diabetes mellitus - Miguel Alexander Ipanaque-Chávez (TUMI Health Sciences Research, 2026)
Introduction: Type 2 diabetes mellitus may lead to peripheral complications that compromise lower-limb integrity and require active patient involvement in prevention. Knowledge, attitudes, and self-care practices are relevant components for identifying preventive behaviors and potential educational needs. Objective: To determine knowledge, attitudes, and practices related to the prevention of peripheral vascular complications among patients with type 2 diabetes mellitus treated at a hospital in Trujillo, Peru, during 2025. Methods: An observational, descriptive, cross-sectional study was conducted among 44 adults with type 2 diabetes mellitus included through census sampling. Information was collected using three structured questionnaires assessing knowledge, attitudes, and preventive practices. Results were summarized using absolute frequencies and percentages. Results: Intermediate knowledge predominated in 68.2% (n = 30) of participants, while 22.7% (n = 10) had high knowledge and 9.1% (n = 4) had low knowledge. Attitudes were favorable in 59.1% (n = 26), somewhat favorable in 31.8% (n = 14), and unfavorable in 9.1% (n = 4). Regarding preventive practices, 61.4% (n = 27) showed good practices, 29.5% (n = 13) regular practices, and 9.1% (n = 4) inefficient practices. Conclusions: Intermediate knowledge, favorable attitudes, and good preventive practices predominated. Nevertheless, the presence of patients with insufficient knowledge and less favorable preventive behaviors identifies areas that may benefit from strengthened education and self-care follow-up.